The Bark Beetle Phloeotribus rhododactylus (Coleoptera: Curculionidae) Has a Stable Range in Europe - Fiala, Tomáš; Holuša, Jaroslav (Insects, 2020)
The bark beetle Phloeotribus rhododactylus feeds mainly on the shrub Cytisus scoparius. The range of P. rhododactylus extends from Spain in the south to southern Sweden, Denmark, and Scotland in the north. Its range to the east extends to Poland, Slovakia, and Hungary, but single localities are known further east in Romania, Bulgaria, and Greece. It is clear that the range of the beetle matches that of its main host. C. scoparius is adapted to Mediterranean and coastal climates, and its range is limited by low winter temperatures. P. rhododactylus is, therefore, rare in Central Europe. It infests either individuals of C. scoparius that have been damaged by mammalian herbivores or snow or that are drought-stressed. Although C. scoparius is an invasive plant in agricultural and natural ecosystems, P. rhododactylus has not been found in any of the areas where C. scoparius has invaded.
Keywords: Cytisus scoparius; bionomics; occurrence; Czech Republic; resource; Scolytinae